Analyzing Communication Strategies used by Junior High School English Teachers in Teaching and Learning Process at the First Grade of SMP Negeri 7 Ternate - Suhaimi Tegamuni; A Armiyati (Program Studi Pendidikan Bahasa Inggris, ISDIK Kie Raha Maluku Utara, 2019)
Communication takes a big role in the teaching and learning process. Communication Strategies act as a tool for solving communication problems. The teachers need to use strategies in communicating to keep conversations with both teachers and students. This research aimed at investigating the type of Communications Strategies (CSs) used by Junior High School English teacher. The data was classified into thirteen strategies based on Dornyei taxonomy. The subjects were two English teachers in the academic year of 2018/2019. This research was descriptive qualitative and the data was collected by observation, interview, and documentation. The results showed that there were five types of Communication Strategies (CSs) found in teaching and learning process used by junior high school English teachers. English teachers used non-linguistic means, code-switching, prefabricated, appeal for help and stalling or time gaining. The use of non-linguistic means was a strategy most often used by the teachers. This is since students still have less knowledge of English. The teachers were expected to use and choose the best strategies to overcome the communication problem in the classroom.